UKURAN PERUSAHAAN, UKURAN DEWAN KOMISARIS, KEPEMILIKAN INSTITUSIONAL, DAN PROFITABILITAS TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Andi Kusuma Negara; Metha Dwi Apriyanti; Hustna Dara Sarra; Sinta Puspita Sari (Jurnal Comparative: Ekonomi dan Bisnis, 2021)
This study aims to examine the effect of company size, board of commissioners size, institutional ownership, and profitability on corporate social responsibility disclosure. The measurement of corporate social responsibility is based on the GRI Guidelines Version 4.0 (2013) to calculate the number of corporate social responsibility disclosures made by companies. The population in this study were food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2012-2015 period. The total sample of this research is 11 companies with 4 years of observation. So, the total sample studied is 44 data. Data analysis was carried out using the classical assumption test and hypothesis testing using multiple linear regression methods. The results of this study indicate that company size has a significant positive effect on CSRD with a t_count value of 7.319 > t_table 2.02619 with a p value of 0.000 <0.05 and institutional ownership has a significant positive effect on CSRD with a t_count value of 2.631 > t_table 2.02619 with p value of 0.012 <0.05, while the board of commissioners size variable has no effect on CSRD with a t_count value of -0.373 < t_table 2.02619 with a p value of 0.711 > 0.05 and profitability has no effect on CSRD with a t_count value of -1.425 < t_table 2.02619 with a p value of 0.163 > 0.05. And company size, board of commissioners size, institutional ownership, and profitability jointly affect CSRD with F_count (14.411) > F_table (2.63) and probability 0.000 < 0.05.